Gold Nanoparticle‐based "Mix and Measure" Fluorimetric Assays to Quantify Antibody Titer. Issue 20 (3rd September 2021) - Sutarlie, Laura; Siak‐Wie Ow, Dave; Kong Ng, Say; Yang, Yuansheng; Su, Xiaodi
Abstract: Monoclonal antibodies (mAbs) for treatment of human diseases are typically human or humanized Immunoglobulin G (IgG) produced in mammalian cell lines. A rapid, less tedious, and high throughput method to quantify mAbs is in demand to accelerate mAb production efficiency. To quantify mAb titer, we developed gold nanoparticle (AuNPs)‐based "mix and measure" fluorimetric assays by exploiting AuNPs' fluorescence quenching ability. The AuNPs are functionalized by an Fc binding protein, i. e. protein G, which binds human IgG and fluorescently labeled rat IgG (Alexa Fluor 488‐rat IgG) with differential affinity. The assays can be in competition or displacement format. The competitive binding of human IgG drug and the labelled rat IgG to protein G‐coated AuNP lead to varied fluorescent intensity that is proportional to the amount of human IgG analte; or the displacement of the labelled rat IgG from protein G‐coated AuNP by human IgG can lead to fluorescent recovery that is also proportionally related to human IgG concentration. The assays can quantify therapeutic mAbs in the range of 10–1, 000 mg/L, demonstrated for Herceptin, Avastin, and Humira in cell culture media. The assays have fast turn over time (within 15 min). They can be performed in microplates and are suitable for high throughput "on‐line" or "at‐line" measurement in mAbs production lines. Abstract : Gold nanoparticle (AuNPs)‐based fluorimetric assays, exploiting AuNPs' fluorescent quenching ability and protein G's differential binding affinity to mAb (human/humanized IgG) and rat IgG. The rat IgG is labelled with a fluorophore. It has a weaker affinity to protein G than human IgG. In the competition assay, the labelled rat IgG competes with human IgG to protein G‐AuNPs coated AuNPs, and the remaining fluorescence intensity of rat IgG is measured. In the displacement assay, the labelled rat IgG bound on protein G‐coated AuNP (fluorescent quenched) is displaced by human IgG drug, leading to fluorescent recovery. The intensity of remaining/recovered fluorescent is proportionally related to human IgG concentration.